2015
DOI: 10.18632/oncotarget.3960
|View full text |Cite|
|
Sign up to set email alerts
|

Trop-2 is up-regulated in invasive prostate cancer and displaces FAK from focal contacts

Abstract: In this study, we show that the transmembrane glycoprotein Trop-2 is up-regulated in human prostate cancer (PCa) with extracapsular extension (stages pT3/pT4) as compared to organ-confined (stage pT2) PCa. Consistent with this evidence, Trop-2 expression is found to be increased in metastatic prostate tumors of Transgenic Adenocarcinoma of Mouse Prostate mice and to strongly correlate with α5β1 integrin levels. Using PCa cells, we show that Trop-2 specifically associates with the α5 integrin subunit, as bindin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
51
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(56 citation statements)
references
References 34 publications
4
51
0
1
Order By: Relevance
“…Of these, several are differentially expressed in certain stages and types of cancers and may be used as diagnostic markers of cancer progression. For example, the tumor‐associated calcium signal transducer 2 was uniquely expressed in prostate cancers in a late stage in comparison with early‐stage prostate cancerous tissues . In our study, laminin α3, β3 and γ2 have been identified as upregulated proteins in LN1‐1 EVs (Figs.…”
Section: Discussionsupporting
confidence: 49%
“…Of these, several are differentially expressed in certain stages and types of cancers and may be used as diagnostic markers of cancer progression. For example, the tumor‐associated calcium signal transducer 2 was uniquely expressed in prostate cancers in a late stage in comparison with early‐stage prostate cancerous tissues . In our study, laminin α3, β3 and γ2 have been identified as upregulated proteins in LN1‐1 EVs (Figs.…”
Section: Discussionsupporting
confidence: 49%
“…Trop2 associates with the α5 integrin subunit, and thereby displaces focal adhesion kinase from focal contacts to promote an invasive phenotype. Consistent with this finding, Trop2 is up-regulated in human prostate cancer (PCa) with extracapsular extension (stages pT3/pT4) as compared to organ-confined (stage pT2) PCa (14-16). Intramembrane proteolysis of Trop2 occurs by the TNFα converting enzyme (TACE) then by γ-secretase.…”
Section: Introductionsupporting
confidence: 59%
“…1C). In recent studies Trop2, which is known to be expressed in a subpopulation of prostate basal cells with stem cell characteristics, was shown to correlate with poor prognosis in prostate cancer (11,16,29). Trop2 is activated by RIP (regulated intra-membrane proteolysis), a mechanism involved in processing and activation of other transmembrane proteins, including N-cadherin and E-cadherin (30).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Уровень TROP2 / TACSTD2 повышен ОНКОУРОЛОГИЯ 4'2017 ТОМ 13 CANCER UROLOGY 4'2017 VOL. 13 118 Обзоры при распространенном РПЖ (стадии pT3 / pT4) по сравнению с локализованным (стадия pT2) [45]. Для Src-киназной индукции ядерного накопления TACSTD2 требуется циклин D1.…”
Section: обзорыunclassified